Treatment of pediatric H-type rectovestibular fistula with tension-free repair of rectal seromuscular layer - Mao Ye; Zhen Chen; Jun Zhang; Cuizhu Feng; Xu Li (Elsevier, 2024)
Objective: This study aimed to assess the outcomes of a 7-year experience with tension-free repair of the rectal seromuscular layer for H-type rectovestibular fistula in female children with a normal anus. Methods: Between May 2016 and January 2023, 86 patients with H-type rectovestibular fistula underwent a standardized surgical procedure conducted by the same surgical team. The procedure involved: (1) Identifying and locating the vestibular orifice. (2) Dissecting the fistula. (3) Dissecting the anterior rectal wall. (4) Repairing the fistula. (5) Closing the internal opening of the fistula. During the dissection of the rectovaginal septum, care was taken to avoid any harm to the posterior wall of the vagina while exposing the anterior rectal wall by 10-25 mm. Results: Follow-up, conducted via telephone or outpatient visits, ranged from 3 months to 6 years and 11 months (median, 3.5 years). In 82 cases (95.35% of 86), primary healing was achieved, resulting in satisfactory perineal appearance, smooth stool passage, and regular defecation. In 4 cases (4.65% of 86), fistula recurrence occurred within 5 to 10 days post-surgery. One case healed within 3 weeks with 3% boric acid sitz baths. The other 2 cases underwent debridement 7 days after the initial operation, leading to successful recovery. The final case experienced a recurrence 1 year after surgery following resection and repair of the perineal fistula, and no further surgical intervention was pursued. Conclusion: Tension-free repair of the rectal seromuscular layer represents a straightforward, safe, and effective surgical approach for managing H-type rectovestibular fistula with a normal anus in female children.